Have we seen the geneticisation of society? Expectations and evidence. Issue 7 (8th March 2017) - Weiner, Kate; Martin, Paul; Richards, Martin; Tutton, Richard
Abstract: Abby Lippman's geneticisation thesis, of the early 1990s, argued and anticipated that with the rise of genetics, increasing areas of social and health related activities would come to be understood and defined in genetic terms leading to major changes in society, medicine and health care. We review the considerable literature on geneticisation and consider how the concept stands both theoretically and empirically across scientific, clinical, popular and lay discourse and practice. Social science scholarship indicates that relatively little of the original claim of the geneticisation thesis has been realised, highlighting the development of more complex and dynamic accounts of disease in scientific discourse and the complexity of relationships between bioscientific, clinical and lay understandings. This scholarship represents a shift in social science understandings of the processes of sociotechnical change, which have moved from rather simplistic linear models to an appreciation of disease categories as multiply understood. Despite these shifts, we argue that a genetic imaginary persists, which plays a performative role in driving investments in new gene‐based developments. Understanding the enduring power of this genetic imaginary and its consequences remains a key task for the social sciences, one which treats ongoing genetic expectations and predictions in a sceptical yet open way.